Penerapan Media Powerpoint Interaktif “Basic Technic Sewing” Pada Mata Kuliah Fashion Design - Mutmainnah, Tri; Marniati, Marniati; Sumbawati, Meini Sondang (CV. Green Publisher Indonesia, 2025)
Interactive PowerPoint is one of the audio-visual media whose preparation refers to learning materials. Interactive PowerPoint media can encourage students to know the material taught more deeply. The objectives of this study are: (1) to describe the learning tools for the application of basic technical sewing interactive powerpoint in fashion design courses, (2) to describe student learning outcomes after applying interactive powerpoint. The methodology in this study is one shot case study and is quantitative. Validation sheets are used to determine the level of accuracy of the learning tools created, as well as psychomotor tests are used to collect information about learning outcomes. The data analysis techniques obtained are described descriptively. The results obtained from this study are (1) validation of learning tools for the application of interactive powerpoint basic technic sewing in fashion design courses conducted by material experts who got the very good category, with an average RPS score of 3.78. As for the interactive power point validation, it was carried out by media experts who were in the very good category, with an average score of 3.63; (2) Student learning outcomes are completed by 94% with the category of very good.